Mini-review on Bubbfil spinning process for mass-production of nanofibers - CHEN,Rou-Xi (2014)
Bubbfil spinning is to use polymers' or melts' bubbles or membranes for fabrication of nanomaterials including smooth nanofibers and discontinuous nanofibers by using electrostatic force, blowing air or mechanical force to overcome the surface tension, it mainly includes the bubble-electrospinning, blown bubble spinning and membrane spinning. The initial ejecting velocity of the Bubbfil spinning process is as high as 100 meters per second. A history of the development of Bubbfil spinning is briefly elucidated, its main properties are emphasized, some effective modifications are discussed for different applications including single bubble electrospinning, blown bubble spinning, air-jet assisted bubble electrospinning, electrostatic-field-assisted blown bubble spinning, and vibration bubble electrospinning which is suitable for melts or high-concentration solutions. Morphology properties are also discussed for different applications.